Cover Picture: Roll‐to‐Roll Slot–Die Coated Organic Photovoltaic (OPV) Modules with High Geometrical Fill Factors (Energy Technol. 8/2015). Issue 8 (August 2015) - Galagan, Yulia; Fledderus, Henri; Gorter, Harrie; 't Mannetje, Hero H.; Shanmugam, Santhosh; Mandamparambil, Rajesh; Bosman, Johan; Rubingh, Jan‐Eric J. M.; Teunissen, Jean‐Pierre; Salem, Ahmed; de Vries, Ike G.; Andriessen, Ronn; et al.
<x xml:space="preserve">Abstract</x> Organic Photovoltaics—Scaling Up Modules with High Geometrical Fill Factor: The cover image demonstrates a flexible semi‐transparent organic photovoltaic (OPV) module manufactured by roll‐to‐roll slot–die coating of functional layers and inkjet printing of the top electrode. One of the biggest challenges towards upscaling and mass production of OPVs is increasing the active area of the modules. Typical slot–die stripe coating provides geometrical fill factors of the modules in the range of 50–75%. In the Full Paper on page 834 by Yulia Galagan and colleagues at Holst Centre and Solliance, the authors demonstrate roll‐to‐roll slot–die coated OPV modules from non‐chlorinated solvents including laser patterning of the coated layers combined with very precise printing of the top electrodes. The combination of laser patterning and high‐resolution printing helps achieve geometrical fill factors of >92.5%. The demonstrated technology shows feasibility for industrial manufacturing of OPV modules of high geometrical fill factor.